Modification & Characterization of Activated Carbon Impregnated with KCl, Na2S, and KI for Enhancing Mercury (Hg) Removal from Natural Gas - Muala, Bahran; Sumarni, Ni Ketut; Puspitasari, Dwi Juli (Department of Chemistry, Faculty of Science and Technology Syarif Hidayatullah Jakarta State Islamic University, 2024)
Modified activated carbon (MAC) has been synthesized and characterized to enhance mercury (Hg) removal from natural gas. MAC was modified by impregnating it into KCl, Na2S, and KI to introduce Cl-, S-, and I- elements. SEM-EDX, FTIR, and SAA were used to characterize the AC and MAC. The isotherm and adsorption capacity were studied using the mercury gas standard. The results of SEM-EDX analysis show that the impregnation method is proven to produce MAC containing elements Cl, S, and I with mass % of 2.78% Cl, 0.76% S, and 39.60% I. The surface area is 421.91 m2/g, the total pore volume is 0.386825 cc/g, and the average pore size is 1.83369 nm. Group functions are -OH, C=C, C=O, C-O, and vibrations at the wavelength number 617.81 cm-1, which the impregnation agent forms. The mechanism for absorbing mercury gas into MAC follows the Freundlich isotherm model, with a coefficient of determination (R2) of 0.996. The adsorption capacity on MAC increased 57 times compared to unmodified activated carbon (AC) from 5540.60 to 315730.64 ng/g, with an efficiency maximum of 100%. The MAC has been proven to enhance mercury adsorption from natural gas with an efficiency of 78.6%.